Reliance Industries Limited and BP Partnership - Reliance Industries Limited (2022)
RIL and bp formally announce the start of Reliance bp Mobility Limited to fuel India’s growing clean energy needs. RIL raises Rs 7,629 crore through Jio-bp partnership.